Pengaruh Pengetahuan Investasi, Modal Minimal, Manfaat Investasi, Dan Literasi Keuangan Terhadap Minat Investasi Mahasiswa Di Pasar Modal - Ni Komang Ersa Santika Widiawati; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2023)
The study targeted student of the Hindu University of Indonesia’s Faculty of Business Economic and Tourism. The purpose of the research was to determine the influence of investment knowledge, minimal capital, benefits and financial literacy on student interest in capital market investement. The populations contained in this study was 364 students in semesters 4 and 6, which then carried out the solvin formula to calculate the number of samples in the study obtained by 78 respondents. The data analysis techniques used are research instrument test, classical assumption tests and multiple linear regression analysis tests. The results of this study found that Investement Knowledge has no significant effect on student investment interest, minimum capital had a positive and significant impact on the student interest. Investment benefits have a positive and significant effect on investment interest and financial literacy has a positive and significand effect on investement interest. The advice that can be given is that students are able to cultivate knowledge about good investments, prepare investment capital, know more benefits that can be given if investing and read more or financial literacy about the development of the capital market.